RESPON MASYARAKAT KELURAHAN LUBUK PUDING DALAM MENONTON SIARAN TV-3 MALAYSIA DI KECAMATAN PULAU BURU KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Helmasari Helma (JURNAL PURNAMA BERAZAM, 2020)
Culture between SIJORI (Singapore-Johor-Riau) has many similarities First Johor Malaysia is almost similar to Malay culture such as Malay Joget, Zapin Melayu, Tanjung Balai Karimun Gazal, Secondly the creation of a constructive Malay cultural pattern imbalances Indonesian culture. Furthermore, the three descendants of Tanjung Balai Karimun in the 1940 era migrated to Malaysia, the Fourth Malay Malay Family originated from Tanjung Balai Karimun, Fifth in terms of Karimun language similar to the Malaysian language at the same time as Malaysia, the Sixth Family (Relationship) visited routine 35 minutes a day to Malaysia using Malaysia Ferry to Malaysia (Johor Bharu) specifically Kukup commuting every one (1) once. So that it is not so difficult for Malaysian television broadcasts to be received and accepted by the majority of the people of Riau Islands, especially in Lubuk Puding Village, Buru Island District, Karimun Regency, which historically has a closeness to the soul of the "Badang" Grave of the legendary Malay Karimun story and Johor Bharu (Kukup / Pontain, Johor ). In terms of Antenna Technology, Indonesian products are easy to get Signal TV3 only using relatively short Antennas of 2.5 meters to 3 meters, they can watch TV3 broadcasts. For that reason, in the type of research the authors describe in the form of structured interviews, which shows the eclectic media they enjoy, namely TV3 because TV3 is almost similar to Malay culture such as Malay Joget, Zapin Melayu, Gazal of Tanjung Balai Karimun, secondly the creation of a constructive Malay culture pattern is imbalanced. Indonesian culture. In that study, researchers used Explanatory Research, only exploratory or personal (in Penzin and Lincoln, Deddy Mulyana and Solatun, 2008: 5). The focus of the research is the Lubuk Puding Village RT 02 RW 08 and RT 03 RW 01 Buru District Karimun Regency, Riau Islands Province. TV3 Malaysia Broadcast, getting a good response shows that the results of the interviews that were distributed, informants answered TV3 Malaysia broadcasts are Malaysian foreign TV broadcasts that have similarities with Malaysians from Buru Island from the dialect / language, culture and food. By watching TV3 Malaysia broadcasts, both entertainment programs and theatrical community of Buru, especially the Lubuk Puding village community, were happy and entertained because the dialect used was easy to understand and understand.